Cerebral venous sinus thrombosis associated with spontaneous heparin-induced thrombocytopenia syndrome after total knee arthroplasty. (3rd October 2021) - Hwang, Steven R; Wang, Yuxiang; Weil, Erika L; Padmanabhan, Anand; Warkentin, Theodore E; Pruthi, Rajiv K
Abstract: Spontaneous heparin-induced thrombocytopenia (HIT) syndrome, characterized by clinical and serologic features of HIT despite the absence of proximate heparin exposure, can be triggered by total knee arthroplasty (TKA). A 56-year-old female receiving aspirin thromboprophylaxis post-TKA presented with aphasia and thrombocytopenia on post-operative day 11. Imaging studies revealed cerebral venous sinus thrombosis (CVST) and intravenous bivalirudin was initiated. Her serum tested strong-positive for IgG anti-PF4/polyanion complexes and serotonin-release assay in the presence and absence of heparin; strong-positive IgG-specific chemiluminescent immunoassay; and moderate-positive latex immunoturbidimetric assay. Two 65 g doses of IVIG were administered. With the improvement of her platelet count, she was transitioned from bivalirudin to warfarin. At one-year follow-up, she remained free of recurrent thrombosis and neurologically stable with a normal platelet count. Previous reports of post-TKA spontaneous HIT syndrome include venous/arterial thrombosis and adrenal hemorrhage, and this report of CVST expands the clinical spectrum of this rare complication of orthopedic surgery.